Pemanfaatan Teknologi Berbasis Aplikasi HIV Info Corner dalam Pencegahan Narkoba dan HIV pada Remaja di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2024 - Erin Padilla Siregar; Sri Rezeki; Amelia Erawaty Siregar; Valentina Sari Theresia Siagian; Wirna Parida (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Introduction: In teenage relationships, casual sex has become commonplace, especially kissing. Drug cases have occurred and been reported. Apart from the high risk of HIV transmission in this region, the role of health workers in preventive measures is still limited to health education or brief outreach through advertisements or pamphlets. This has resulted in a lot of misunderstanding of information about HIV, especially in terms of prevention. So a comprehensive health education strategy regarding HIV is needed taking into account technological advances that are easily accessible and reliable. The application used for HIV prevention programs in adolescents is HIV Info Corner. This application contains comprehensive educational material about HIV, HIV risk behavior, and issues surrounding adolescent problems. Apart from that, this application is equipped with a consultation chat room so that teenagers can ask questions and discuss directly about HIV and HIV risk behavior. Teenagers are encouraged to download and install the HIV Info Corner application and use it and read the information or content contained in it. Of the 20 teenagers, there are 15 teenagers who do not know about the benefits of the HIV Corner application in Bangun Rejo village, therefore health education is needed about the use of application-based technology in preventing HIV AIDS in teenagers, with the hope that teenagers can use the HIV prevention application and spread it to teenagers who have not received this information.